Customer focus in UK e-Government: Or, putting the politics back into e-Government - James Cornford; Paul Richter (International Journal of Business Science & Applied Management (IJBSAM), 2007)
The techniques and technologies of customer service, as introduced under the guise of e-government, have brought certain aspects of public service users into sharp focus, but at the expense of other aspects. It is hypothesised that this effect may lie behind the failure of half a decade of IT-enabled change in public services to improve "customer satisfaction". Remedying this situation, it is suggested, will require a re-examination of the model of the customer which underpins customer service as it has been adopted by public service organisations.
Keywords: 650; e-government; public services; customer service; representation; CRM